Somatometric Indicators And Somatotypological Characteristics Of School Teachers Living In Rural Areas - Khatamov, A.; Tuymachev, U; Ubaydullayev, R.; Inoyatov, A.; Ibragimov, I. (Journal of Neonatal Surgery, 2025)
This study investigates the somatometric indicators and somatotypological characteristics of school teachers residing in rural areas. The research aims to identify the physical characteristics, body composition, and somatotype profiles of rural teachers and explore the relationship between these factors and the lifestyle common in rural settings. Using a sample of 150 teachers, various somatometric measurements, including height, weight, body mass index (BMI), and waist-to-hip ratio, were taken. Additionally, the somatotype classification was determined using Sheldon’s somatotype method. The findings reveal a predominance of endomorphic and mesomorphic body types among teachers, with specific tendencies linked to the physical demands of rural living, such as increased physical labor and limited access to healthcare. The results highlight the importance of understanding the physical profiles of rural schoolteachers to better inform health policies and workplace interventions designed to promote overall well-being in rural educational environments.